Oral Hygiene and Periodontal Health Status of Urban Population of Kathmandu District: A Pilot Study - Bhattarai, Rosina; Khanal, Sunita; Rao, G. Nagaraja; Dhami, Bhageshwar; Gupta, Sujaya (Journal of Nepalese Society of Periodontology and Oral Implantology, 2017)
Background: Healthy teeth, their supporting structures and gingiva play an important role in oral health. Gingivitis progresses to periodontitis in a phased manner causing continuous deterioration. In severe cases, removal of the tooth becomes inevitable. Hence, if gingivitis and periodontitis can be identified and treated earlier, tooth loss can be minimized. Aim: To assess the status of oral hygiene, gingival and periodontal health of Urban population of Kathmandu district. Materials and methods: Data on cross-sectional study of 252 individuals was collected using pre-designed survey form utilizing Gingival Index, Oral Hygiene Index–Simplified and Community Periodontal Index. Collected data was analyzed using SPSS version 20. Results: An urban population of 126 males and 126 females were examined in Kathmandu for this survey. In this study, 55.6% were of age-group 20-39 years while 44.4% were of 40-60 years, 35.31% and 54.76% of individuals had good and fair oral hygiene respectively & 49.20% of them had deposition of calculus and 25% had loss of attachment of 4-5mm. Only 16.6% were having healthy gingiva whereas 52.38% had mild and 26.5% had moderate gingivitis. Statistically significant results of all above are seen with advancement of age (p<0.05). Conclusion: Results show that gingival and periodontal diseases are widely distributed in urban population. Hence, appropriate preventive and periodic therapies should be employed.